STRUCTURAL MODELING, EXPRESSION AND PURIFICATION OF CHIMERIC CHITINASE42 CONTAINING HIS-TAG IN NICOTIANA TABACUM HAIRY ROOT SYSTEM: STRUCTURAL MODELING, EXPRESSION AND PURIFICATION - Motallebi, Mostafa; Soleimani, Faranak; Zamani, Mohammadreza; Jourabchi, Esmat (Journal of Agricultural Sciences (Belgrade), 2023)
Chimeric chitinase42 (Chit42 containing ChBD) has great potential as a candidate for digesting and recycling chitin as a beneficial nutrient, which can be produced in bioreactors. The plant is one of the efficient bioreactors which can produce the eukaryotic proteins in active forms. A suitable platform for easy, cost-effective, and fast expression of different recombinant proteins is provided by the plant hairy roots system. Due to the huge amount of proteins in plants, His-tag can be used to facilitate the purification of recombinant proteins. In this research, different computer programs were used for the analysis of the three-dimensional structure of chimeric chitinase42 containing His-tag. The results showed that these comparative modelings have a remarkable degree of accuracy in predicting the fused protein structure. The Z-score of -9.38 and -3.64 predicted for chit42 and CHBD by ProSA represent the good quality of the model. Also, bioinformatics observations showed that His-tag was exposed and can be used to purify chimeric chitinase42. The chimeric chitinase42 containing His-tag was expressed in Nicotiana tabacum hairy roots, and the role of His-tag in the detection by western blot and purification using Ni-NTA column was investigated. The presence of chimeric chitinase42 was verified by SDS-PAGE and western blot analysis of root extracts. The purification step was achieved using His-tag and Ni-NTA column. The biological activity of the plant-derived chimeric chitinase42 was confirmed by investigating the chitinase activity of purified protein on the media plate containing the colloidal chitin.
Keywords: chimeric chitinase42, His-tag, tobacco hairy root, structural modeling